Development of Guided Inquiry-based E-Worksheet to Stimulate Science Process Skills on Light Diffraction Materials - Handayani, Meita Puteri; Munna, Kamila; Herlina, Kartini; Suyatna, Agus; Viridi, Sparisoma (JURNAL EKSAKTA PENDIDIKAN (JEP), 2025)
Understanding light diffraction requires higher-order thinking and the ability to apply science process skills. Therefore, this study aims to develop a guided inquiry-based e-worksheet that is valid, practical, and effective to stimulate science process skills in Light Diffraction materials. The study uses the Design and Development Research (DDR) approach, which consists of four stages: analysis, design, development, and evaluation. The data analysis uses a validity test assessed by three experts, a practicality test conducted by students and teachers, and an effectiveness test as measured by the N-Gain test. The validity test results obtained an average value of 3.54, which is "very valid" category. The e-worksheet’s design and content correspond to the science process skill: formulating problems, formulating hypotheses, conducting experiments, drawing conclusions, and discussing. The practicality test produced an average student response result of 86% and an average teacher perception result of 88%, both of which are classified as "very practical." The effectiveness test produced an N-Gain value of 0.71 in the experimental class, which is classified as high and increased compared to the control class's value of 0.49, which is classified as moderate. Hence, an e-worksheet based on guided inquiry has been produced to stimulate valid, practical, and effective science process skills. The results contribute to the theoretical understanding of guided inquiry-based learning and provide practical guidance for teachers in implementing digital inquiry activities on light diffraction.